Detection of the Contribution of Vegetation Change to Global Net Primary Productivity: A Satellite Perspective - Xiaoqing Hu; Huihui Feng; Yingying Tang; Shu Wang; Shihan Wang; Wei Wang; Jixian Huang (Remote Sensing, 2024)
Exploring NPP changes and their corresponding drivers is significant for the achievement of sustainable ecosystem management and in addressing climate change. This study aimed to explore the spatiotemporal variation in NPP and analyze the effects of vegetation and climate change on the global NPP from 2003 to 2020. Methodologically, the Theil–Sen and Mann–Kendall methods were used to study the spatiotemporal characteristics of global NPP change. Moreover, a ridge regression model was built by selecting the vegetation indicators of the leaf area index (LAI) and fraction vegetation coverage (FVC) and the climate factors of CO2, shortwave downward solar radiation (Rsd), precipitation (P), and temperature (T). Then, the relative contributions of each factor were evaluated. The results showed that, over the previous two decades, the global mean NPP reached 503.43 g C m−2 yr−1, with a fluctuating upward trend of 1.52 g C m−2 yr−1. The regions with a significant increase in NPP (9.22 g C m−2 yr−1) were mainly located in Central Africa, while the regions with decreasing NPP (−3.21 g C m−2 yr−1) were primarily in the Amazon Rainforest in northern South America. Additionally, CO2, the LAI, and the FVC exhibited positive contributions to the NPP trend, with the predominant factors being CO2 (relative contribution of 32.22%) and the LAI (relative contribution of 21.96%). In contrast, the contributions of Rsd and precipitation were relatively low (<10%). In addition, the contributions varied at different land cover and climate zone scales. The CO2, LAI, FVC, and temperature were the predominant factors affecting NPP across the vegetation types. At the scale of climate zones, CO2 was the predominant factor influencing changes in vegetation NPP. As the climate gradually transitioned towards temperate and cold regions, the contribution of the LAI to NPP increased. The findings of this study help to clarify the effects of vegetation and climate change on the ecosystem, providing theoretical support for ecological environmental protection and other related initiatives.